Are Women as Competitive as Men in Road Races? - Johnson, Jennifer; Magel, Rhonda (Journal of Sports Research, 2016)
Samples of road races are taken for various distances, including 5K, 10K, half-marathon, and marathon. Age/gender adjusted times are calculated for each runner of every road race included in the samples. Hypothesis tests are conducted comparing the average age/gender adjusted running time for men with the age-gender adjusted time for women for each race in the sample and then using meta-analysis techniques to collectively compare the mean adjusted times for each of the various distances. Hypothesis tests are also conducted comparing the variances of the age/gender adjusted running times for women with the variance of the age/gender adjusted running times for men, as well as the proportions of men and women who have age/gender adjusted running times greater than the 60th percentile, and then less than the 40th percentile. Overall, the average age/gender adjusted running times for women are less than those of men for each of the distances. It is found that a significantly higher proportion of men perform at or above the 60th percentile compared to the proportion of women for each of the race distances. It is found, however, that the variances of the age/gender adjusted running times for men are larger.